Research on the Online Learning Experience of South Asian Students during COVID-19: The Mediating Effect of Online Learning Status on Autonomous Learning and Learning Effect Evaluation - Yu, Lan; Xu, Lingying (Journal of International Students, 2022)
COVID-19 has influenced the flow of international students and their learning experience continuously and deeply. Teaching Chinese as a foreign language to international students during the COVID-19 faces unprecedented challenges and opportunities. Based on the review of the literature on online Chinese teaching, this research explored the online learning experience of a group of South Asian students in China during the pandemic. Adopting the questionnaire method, the results revealed the participants’ overall positive online learning status and evaluation of the online learning effect. In addition, this research showed that the participants’ autonomous learning, reflected by their cognition and attitude towards learning, had a significant impact on learning effect evaluation, mediated by online learning status. Suggestions for teaching and management are given to support the incorporation of online and offline Chinese education during the pandemic.